THE FIRST EXPERIENCE OF DESIGN AND IMPLEMENTATIONOF POST-GRADUATE TRAINING AND PROFESSIONAL DEVELOPMENT OF FACULTY MEMBERS PROGRAMS AS PROGRAMS OF THE THIRD LEVEL OF HIGHER EDUCATION: IDENTIFIED ISSUES AND FEASIBLE SOLUTIONS - Evgeniya V. Karavaeva; Vladimir V. Malandin; Sergey A. Pilipenko; Irina G. Teleshova (Высшее образование в России, 2016)
This article presents the results of expert analysis of post-graduate programs developed on the basis of the FSES: it systematizes problems that educational and research institutions face when design post-graduate programs, describes approaches to theimplementation of post-graduate programs organized in a systematic way - the experience of the Faculty of Economics, Lomonosov Moscow State University, and of Moscow Pedagogical State University; states a number of debatable suggestions on content-related updating of the very model of post-graduate studies as the third level of higher education.